Palopo United Football School Development Management - Muh Fillah A; rasyidah jalil; hadi pajarianto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Football is a game which has must be improved, both individuals, adults and young people who have played it and made football become the most famous game on the planet. The location of the research was carried out at the Gaspa Palopo field, carried out at 09.30 WITA, August 18, 2024. This research is a qualitative study aim in obtaining an overview and analyzing the implementation of the management function of football sports training at the Palopo United football school (SSB). The sample in this study are Coaches, Administrators, and Students of the Football School (SSB) from Palopo City. The researcher will examine the Chairman of SSB Palopo United, 2 coaches and 5 students of SSB Palopo United. Qualitative research, where the data is not in the form of numbers, more in the form of narratives, descriptions, stories, written and unwritten documents. This research was conducted at the Gaspa field, Palopo City, South Sulawesi. In this study, the subject is the Palopo United Football School where the sample is the Chairman of SSB Palopo United, the Coach and the Students of SSB Palopo United. The results of the interviews that the resercher have obtained on the sample managers and coaches are the shortcomings of SSB Palopo United are the lack of facilities, infrastructure and facilities such as fields and tools for training, such as balls, cones, kuns and other tools. Based on the results of the research that has been done, it is known that the number of this research samples is 3 from the management of SSB Palopo United, which are 1 chairman or manager and 2 coaches then 5 samples from SSB Palopo United students, with the results of the interview where all the answers are almost the same, there are only slight differences. Thus it can be concluded that SSB Palopo United is now, which was previously not developed, now has begun to develop rapidly in terms of their training facilities, SSB students who are starting to increase and experienced coaches who already have a National D License and an official National C License from the AFC.